Controlled Signaling—Insulin-Like Growth Factor Receptor Endocytosis and Presence at Intracellular Compartments - Rieger, Leonie; O’Connor, Rosemary (Frontiers in Endocrinology, 2021)
Ligand-induced activation of the IGF-1 Receptor triggers plasma-membrane-derived signal transduction, but also triggers receptor endocytosis, which was previously thought to limit signaling. However, it is becoming ever more clear that IGF-1R endocytosis and trafficking to specific subcellular locations can define specific signaling responses that are important for key biological processes in normal cells and cancer cells. In different cell types, specific cell adhesion receptors and associated proteins can regulate IGF-1R endocytosis and trafficking. Once internalized, the IGF-1R may be recycled, degraded or translocated to the intracellular membrane compartments of the Golgi apparatus or the nucleus. The IGF-1R is present in the Golgi-apparatus of migratory cancer cells where it signaling contributes to aggressive cancer behaviors including cell migration. The IGF-1R is also found in the nucleus of certain cancer cells where it can regulate gene expression. Nuclear IGF-1R is associated with poor clinical outcomes. IGF-1R signaling has also been shown to support mitochondrial biogenesis and function, and IGF-1R inhibition causes mitochondrial dysfunction. How IGF-1R intracellular trafficking and compartmentalized signaling is controlled is still unknown. This is an important area for further study, particularly in cancer.